Characterization of plasma electrolytic oxidation coating on low carbon steel prepared from silicate electrolyte with Al nanoparticles. Issue 18 (15th December 2017) - Yang, Wenbin; Liu, Weimin; Peng, Zhenjun; Liu, Baixing; Liang, Jun
Abstract: The plasma electrolytic oxidation (PEO) coatings were prepared on low carbon steel from silicate electrolyte without and with Al nanoparticles, respectively. The structure, composition, anti-wear and anti-corrosion properties of the PEO coatings were investigated. The results indicated that the Al nanoparticles in the silicate electrolyte turned into alumina during the PEO process and reduced the amount of iron oxides in the coating. The PEO coating prepared from silicate electrolyte with Al nanoparticles showed enhanced wear resistance due to the formation of alumina. Furthermore, the coating was characterized by sealed pores on the surface, different from the open pores on the surface of PEO coating prepared from silicate electrolyte without Al nanoparticles. The modified structure and the changed composition of PEO coating by introducing Al nanoparticles in the electrolyte significantly improved the corrosion resistance of the coating, demonstrated by the electrochemical corrosion and salt spray tests.